Cleavage of Mer Tyrosine Kinase (MerTK) from the Cell Surface Contributes to the Regulation of Retinal Phagocytosis - Law, Ah-Lai (J Biol Chem, 2015)
Phagocytosis of apoptotic cells by macrophages and spent photoreceptor outer segments (POS) by retinal pigment epithelial (RPE) cells requires several proteins, including MerTK receptors and associated Gas6 and protein S ligands. In the retina, POS phagocytosis is rhythmic, and MerTK is activated promptly after light onset via the αvβ5 integrin receptor and its ligand MFG-E8, thus generating a phagocytic peak. The phagocytic burst is limited in time, suggesting a down-regulation mechanism that limits its duration. Our previous data showed that MerTK helps control POS binding of integrin receptors at the RPE cell surface as a negative feedback loop. Our present results show that a soluble form of MerTK (sMerTK) is released in the conditioned media of RPE-J cells during phagocytosis and in the interphotoreceptor matrix of the mouse retina during the morning phagocytic peak. In contrast to macrophages, the two cognate MerTK ligands have an opposite effect on phagocytosis and sMerTK release, whereas the integrin ligand MFG-E8 markedly increases both phagocytosis and sMerTK levels. sMerTK acts as a decoy receptor blocking the effect of both MerTK ligands. Interestingly, stimulation of sMerTK release decreases POS binding. Conversely, blocking MerTK cleavage increased mostly POS binding by RPE cells. Therefore, our data suggest that MerTK cleavage contributes to the acute regulation of RPE phagocytosis by limiting POS binding to the cell surface.